Influence of surface energy and elastic strain energy on the graphene growth in chemical vapor deposition - Sirat, Mohd Shukri; Ismail, Edhuan; Ramlan, Amir Hakimi; Fauzi, Fatin Bazilah; Yaacob, Iskandar Idris; Mohamed, Mohd Ambri; Mohd Abid, Mohd Asyadi Azam; Ani, Mohd Hanafi (Elsevier Ltd., 2019)
Polycrystalline metal substrates such as copper (Cu) have been intensively used to grow graphene in chemical vapor deposition (CVD) technique. It has been observed that crystal orientations affect the quality of graphene produced to some degree. The existence of crystal orientations caused graphene to grow randomly on top of Cu which also resulted on the formation of polycrystalline graphene. Despite this, the influence of crystal orientations on the quality of graphene produced are not yet fully understood. There are two possible factors that could affect graphene growth from crystal orientation point of view; surface energy and elastic strain energy. The understanding towards these both factors might beneficial to control the quality of graphene. This paper thus aims to highlight the influence of surface energy and elastic strain energy on the graphene growth in CVD. Substrate used were single crystal Cu with (111), (110) and (100) orientations. The graphene was grown inside a closed reaction chamber with the presence of argon (Ar), hydrogen (H2) and methane (CH4) gases with partial pressure ratio of 0.6: 0.2: 0.2 at 1 atm, 1000 ˚C in 30 minutes. The quality of the as-grown graphene was identified using Raman spectroscopy. The Raman spectra show the existence of graphene peak for all the Cu substrates. The calculation of ID/IG ratio revealed that the Cu (100) possessed the lowest amount of defects compared to Cu(110) and Cu(111). While I2D/IG ratio fluctuated between 0.22 to 0.34 suggested that the crystal orientation does not control the thickness of graphene layer at these reaction conditions. The usage of higher CH4 partial pressure produced a thicker graphene. It is assumed that the thickness of the graphene exceeded the critical thickness thus elastic strain energy becomes the dominant factor in controlling graphene growth. Larger lattice mismatch causes major defects on graphene and this result has been shown in graphene grown on top of Cu(111). These findings thus would give a new insight to tailor the high-quality large-area graphene growth in CVD.